Root Cause Analysis of Delays in The XYZ Toll Road Design and Construction Project using the RCA Method - Yayuk Sri Rahayu; Farida Rachmawati (Politeknik Siber Cerdika Internasional, 2025)
The XYZ Toll Road Construction Design and Construction Project Plan is a continuation of the Solo – Ngawi Toll Road which is part of the Trans Java Toll Road series and part of a program that was delayed due to the 1997 monetary crisis. Judging from the chronology of the contract journey, this project experienced a non-excusable without compensable delay where the planned handover was on June 6, 2025 to November 30, 2026. The purpose of this study is to identify the main factors that cause delays, find out the root causes of the delays and provide recommendations and solutions that can be applied to minimize delays in the design project. The research method used in this study is a qualitative descriptive method by collecting data through a questionnaire technique. This study will discuss the application of the Root Cause Analysis (RCA) method, namely: pareto diagran, fishbone (Ishikawa diagram) and 5WHYS to identify the root of the problem. The root of the problem causing the delay is that when the contract is signed, the land acquisition is 0% so that the land handover is carried out in stages during the implementation, some locations have geographical conditions that are not possible to pass so that it is necessary to shift the road trajectory and at the time the project is running, the owner/employer is still carrying out the financial closing process. The final results of the research set strategies and managerial implications to accelerate decision-making, reduce overlapping responsibilities, ensure continuity of information from design to construction, strengthen cost, quality, and time control in an integrated manner.